MSMEs Development Through QRIS Islamic Banking in Medan City, Indonesia - Rahmayati; Mujiatun, Siti; Affandi, Ahmad (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
The purpose to examine the use of QRIS whether it is able to increase the income of MSMEs in the city of Medan, Indonesia. The novelty recommendations for the use of QRIS for MSMEs in Medan City. The type of research uses primary research techniques by collecting data directly in the field, namely the respondents are MSME actors in Medan City. The Implication can Providing input to MSMEs to use QRIS because it can increase their income and Islamic banks to improve QRIS product innovation, especially risk mitigation and real time.The results showed that the increase in MSME income in Medan City stated that the use of the QRIS payment system had a positive and significant effect on increasing MSME income in Medan City. Constraints from using QRIS for MSMEs There are still those who do not understand how to use QRIS, both from business actors and their customers; network constrained; the slow process of disbursing funds in real time; and there is a fee for using QRIS that is charged to merchants.